A rare fatality due to calcified stylohyoid ligament (Eagle syndrome). (June 2017) - Gupta, Avneesh; Aggrawal, Anil; Setia, Puneet
The elongation or calcification of the stylohyoid ligament that leads to pressure symptoms, or entrapment of nearby glossopharyngeal nerve or carotid artery, is known as Eagle syndrome. A PubMed search leads to finding of rare fatality among the 49 reported cases. In the present case, the deceased was a 40-year-old male who choked on his food. We hypothesise that the impaction of food in the upper respiratory tract, as well as the inability to intubate the person, were both the result of the calcified stylohyoid ligament.